2005
DOI: 10.1152/ajpgi.00211.2004
|View full text |Cite
|
Sign up to set email alerts
|

P2X and P2Y purinergic receptors on human intestinal epithelial carcinoma cells: effects of extracellular nucleotides on apoptosis and cell proliferation

Abstract: . P2X and P2Y purinergic receptors on human intestinal epithelial carcinoma cells: effects of extracellular nucleotides on apoptosis and cell proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 63 publications
(113 reference statements)
7
104
2
1
Order By: Relevance
“…In addition, P2Y 1 , P2Y 2 , and P2X 1-7 receptor proteins are expressed in these cells. Functional studies on cell proliferation and apoptosis using selective agonists and antagonists suggested involvement of P2X 7 , P2Y 1 , P2Y 2 , and P2Y 4 receptors but their role in secretion awaits further study [31].…”
Section: Mucosal Epithelial Cell Lines and Ion Transportmentioning
confidence: 99%
“…In addition, P2Y 1 , P2Y 2 , and P2X 1-7 receptor proteins are expressed in these cells. Functional studies on cell proliferation and apoptosis using selective agonists and antagonists suggested involvement of P2X 7 , P2Y 1 , P2Y 2 , and P2Y 4 receptors but their role in secretion awaits further study [31].…”
Section: Mucosal Epithelial Cell Lines and Ion Transportmentioning
confidence: 99%
“…P2 receptors, which are comprised of P2X (ionotropic) and P2Y (metabotropic, G-protein-coupled) subtypes, respond to a variety of nucleotide agonists. The role of P2 receptors, particularly P2X receptors, in apoptosis has been demonstrated in both non-neuronal and neuronal cells, including most prominently the P2X 7 receptor in initiating spinal neuron apoptosis (Franke et al, 2004;Wang et al, 2004;Coutinho-Silva et al, 2005). In contrast, the role of P2Y receptors in neuronal apoptosis remains mostly unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…P2Y receptors have been linked to either induction/suppression of apoptosis or hypoxic stress and proliferation (Kim et al 2003a, Yitzhaki et al 2005, Coutinho-Silva et al 2005.…”
mentioning
confidence: 99%